Experiential Education for Quality of Aging (Training and Practice : Journal of Educational Sciences, 2017)
experienced among the elderly people, which offer new experience, development possibilities for the old as well. Within the framework entitled Sample programme for quality ageing (Mintaprogram a minőségi időskorért) we have planned a series of experiential education practice training consisting of 5 sessions in Alsómocsolád for the residents of Autumn Light Old People’s Home (Őszi Fény Idősek Otthona). Because of the several barriers which characterised the elderly we have chosen activities first of all in which almost everybody could participate. We have experienced that the hours spent happily in affectionate atmosphere filled the elderly up, they participated in the tasks with pleasure, changing of the daily routine was not a problem for them, moreover variation thrilled them. Concerning the methodology of experiential education, the special age group had to be taken into consideration, which was different mainly not from the point of view of the tasks given to them, but the time spent on their solution and the attention paid on individuals compared to the infant age group. Although experiential education – if we insist on the word for word translation of pedagogy – is for children, still according to our observations so far it has been succesful in case of every age group, including the elderly.